MODERN MUSIC PROFESSIONALLY LIMITED VOCABULARY IN THE SYSTEM OF THE ENGLISH LANGUAGE - (:unkn) unknown (Видавничий дім «Гельветика», 2020)
The absence of clear criteria for distinguishing between different layers of professionally limited vocabulary in the system of the language is an explanation of so many differences in the treatment of terms, professionalisms, jargonisms and slang. The suggested working definitions of these groups of special vocabulary is an attempt to overcome this difficulty. It is necessary to pay more attention to the criteria for stylistic differentiation of professionally limited vocabulary. The present research is based on I. R. Halperin’s concept and understanding of regarding professionally limited vocabulary. Having defined the groups of special music vocabulary the analysis of 50 units was undertaken with the result of its constituting 4,16% of all 1200 words in I. Ayto’s “The Longman Register of New Words”, 1987. According to the types of formation single words, compounding derivation prevail, words are more in number than word combinations. As to the parts of speech, the majority of words are nouns, formal words prevail over informal. Among the units there can be found borrowings from other languages: Latin and Hindi; French and Italian suffixes can be traced. Words from other sphere enter the music vocabulary and vice versa. Regional variants are represented by Americanisms. Some words become outdated due to the innovative technologies and rapid technological progress. Contextual analysis proved that only some words have positive implication, but mostly they are used with negative one. In the informative style the analysed words are used with the aim of informing the readers and listeners about the news in music world. Some stylistic devices can be found in the context created with the help of music words: morphologic repetition, antithesis, metaphor, from the syntactical point of view one-member exclamatory sentence with music word can be found. The perspective of research is the investigation of music professionally limited vocabulary in belleslettres and colloquial functional styles
Keywords: music; terms; jargonism; professionalism